Radioluminescence from Tc-99m in glass predicts local dose. (October 2017) - Ackerman, Nicole L.; Boschi, Federico; Spinelli, Antonello E.
Highlights: Tc-99m produces visible light in glass via a process other than the Cerenkov effect. Monte Carlo results show agreement between light and dose. Radioluminescence can be used for real-time dosimetry from Tc-99m in transparent materials. Abstract: The widely-used gamma-emitter Tc-99m has been shown to lead to optical emissions in mice and glass. We investigated the possibility that these emissions are due to the Cerenkov effect and whether the light emitted is proportional to local dose. By using a Geant4 Monte Carlo model matched to an experimental measurement, we show that the light detected by a small animal optical imaging system provides a 2D map of the dose throughout a glass sample. We conclude that radioluminescence from Tc-99m can be used to quantitatively measure dose in transparent materials, which could have applications in dosimetry and quality assurance.